Interactive effects between soil properties and bacterial communities in tomato rhizosphere under the application of microbial agents - Longxue Wei; Dongbo Zhao; Lianghai Guo; Jianjun Guo; Jinying Zhu; Yanting Pei; Peiyan Guan; Zhihui Guo; Huini Cui; Jiansheng Gao; Yongjun Li; Liang Zhang; et al. (PeerJ)
Background The purpose of this study was to determine the impact of microbial agents on physicochemical properties, enzyme activities, and bacterial communities in tomato (Solanum lycopersicum L.) rhizosphere soil in order to provide a theoretical foundation for the stability of tomato rhizosphere soil microecology and the ecological preservation of farmland soil. Methods Tomato rhizosphere soils treated with various microbial agents, as well as an untreated control (FQ_CK), were analyzed. The effects of different microbial agents on the physicochemical properties, enzyme activities, and bacterial community structure of tomato rhizosphere soil after 2 years of continuous cropping were analyzed using 16S rRNA high-throughput sequencing technique. Results With the application of microbial agents, microbial agent treatment (Bacillus subtilis (FQ_T1), Trichoderma harzianum (FQ_T2), Bacillus amyloliquefaciens (FQ_T3), Verticillium thuringiensis (FQ_T4), and Verticillium purpureum (FQ_T5)) was beneficial for improving the physicochemical properties and enzyme activity of tomato rhizosphere soil after 2 years of continuous cropping. Compared with the control FQ_CK, bacterial treatment increased the richness of bacterial communities, total number of species, and overall relative abundance of beneficial bacterial phylum and genus, to a certain extent. It had a positive impact on microbial structure and function, improved the interaction and stability of species ecological networks, and was conducive to the stability and sustainability of tomato rhizosphere soil microbial ecosystem functions.